‘n Literêre ondersoek na die teologiese boodskap van Eksodus 2:1–10 - Snyman, Stephanus Daniel (Stellenbosch Theological Journal, 2025)
This article presents a literary investigation of Exodus 2:1–10 to probe the theological message the passage might have. A theological message of this passage is not at once evident as God is seemingly absent in this narrative. Consequently, little attention has been paid to the theological message of Exodus 2:1–10. The method chosen is to read the text from a literary perspective. It is widely acknowledged that Exodus 2:1–10 is a captivating narrative that is brilliantly told. The investigation reveals a chiastic structure, and the literary device of irony used. The investigation shows that ordinary human beings may devise plans to survive pressing times, that God is present even when it is difficult if not impossible to see him at work and thirdly that there is a larger picture unable for human beings to see or comprehend.